Associations between Functional Connectivity Dynamics and BOLD Dynamics Are Heterogeneous Across Brain Networks - Fu, Zening; Tu, Yiheng; Di, Xin; Biswal, Bharat B.; Calhoun, Vince D.; Zhang, Zhiguo (Frontiers in Human Neuroscience, 2017)
Functional brain imaging has revealed two types of dynamic patterns of brain in the resting-state: the dynamics of spontaneous brain activities and the dynamics of functional interconnections between spontaneous brain activities. Although these two types of brain dynamics are usually investigated separately in the literature, recent functional magnetic resonance imaging (fMRI) studies have shown that they exhibit similar spatial patterns, suggesting the dynamics of spontaneous brain activities and the dynamics of their interconnections are associated with each other. In this study, we characterized the local blood oxygenation level dependent (BOLD) dynamics and the functional connectivity (FC) dynamics in the resting-state, and then investigated their between-region associations. Time-varying FC was estimated as time-varying correlation coefficients using a sliding-window method, and the temporal variability of BOLD and time-varying FC were used to quantify the BOLD dynamics and the FC dynamics, respectively. Our results showed that the BOLD dynamics and the FC dynamics exhibit similar spatial patterns, and they are significantly associated across brain regions. Importantly, such associations are opposite for different types of FC (e.g. within-network FC dynamics are negatively correlated with the BOLD dynamics but the between-network FC dynamics are positively correlated with the BOLD dynamics), and they are spatially heterogeneous across brain networks. The identified heterogeneous associations between the BOLD dynamics and the FC dynamics appear to convey related or even distinct information and might underscore the potential mechanism of brain coordination and co-evolution.